The Influence of Profitability, Sales Growth, Asset Structure, and Liquidity on Capital Structure in Food and Beverage Sub-Sector Companies Listed on the Indonesia Stock Exchange 2021-2023 - Desi Syafitri; Fauzan Fauzan (Universitas KH. Abdul Chalim Mojokerto, 2025)
This study examines the influence of profitability, sales growth, asset structure, and liquidity on capital structure in food and beverage sub-sector companies listed on the Indonesia Stock Exchange from 2021 to 2023. A quantitative research approach is employed using secondary data from financial reports obtained through documentation techniques. The sample selection follows purposive sampling criteria, ensuring data completeness and consistency. Capital structure, measured by the Debt to Equity Ratio (DER), serves as the dependent variable, while independent variables include profitability, sales growth, asset structure, and liquidity. The research methodology encompasses descriptive statistics, classical assumption tests (normality, multicollinearity, homoscedasticity), multiple linear regression analysis, and hypothesis testing. The results indicate that profitability and sales growth significantly influence capital structure, supporting H1 and H2. Conversely, asset structure does not exhibit a significant effect, leading to the rejection of H3. Liquidity significantly impacts capital structure, confirming H4.